The Cold War in the Middle East : regional conflict and the superpowers, 1967-73 - Ashton, Nigel John. (London ; New York : Routledge, 2007)
This edited volume re-assesses the relationship between the United States, the Soviet Union and key regional players in waging and halting conflict in the Middle East between 1967 and 1973. These were pivotal years in the Arab-Israeli conflict, with the effects still very much in evidence today. In addition to addressing established debates, the book opens up new areas of controversy, in particular concerning the inter-war years and the so-called 'War of Attrition', and underlines the risks both Moscow and Washington were prepared to run in supporting their regional clients. The enga.
Preface -- Introduction : the Cold War in the Middle East, 1967-73 / Nigel J. Ashton -- The Cold War and the Six Day War : U.S. policy toward the Arab-Israeli crisis of June 1967 / Peter L. Hahn -- The politics of stalemate : the Nixon administration and the Arab-Israeli conflict, 1969-73 / Salim Yaqub -- The Cold War and the Soviet attitude toward the Arab-Israeli conflict / Galia Golan -- Israel's traumatic pre-1967 war experience and its implications for Israel's foreign policy decision-making in the post-war period / Zaki Shalom -- Military/political means/ends : Egyptian decision-making in the War of Attrition / Laura M. James -- How American and Israeli intelligence failed to estimate the Soviet intervention in the war of attrition / Dima P. Adamsky -- The origins of a misnomer : the 'expulsion of Soviet advisers' from Egypt in 1972 / Isabella Ginor and Gideon Remez -- The 'Big Lie' and the gGreat Betrayal' : explaining the British collapse in Aden / Spencer Mawby -- Cold war, hot war and civil war : King Hussein and Jordan's regional role, 1967-73 / Nigel J. Ashton.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Middle East -- Foreign relations -- United States; United States -- Foreign relations -- Middle East; Middle East -- Foreign relations -- Soviet Union; Soviet Union -- Foreign relations -- Middle East; Cold War; Arab-Israeli conflict -- 1967-1973.; Moyen-Orient -- Relations extérieures -- États-Unis.; États-Unis -- Relations extérieures -- Moyen-Orient.; Moyen-Orient -- Relations extérieures -- URSS; Guerre froide; Conflit israélo-arabe -- 1967-1973.; HISTORY -- General; Arab-Israeli conflict; Diplomatic relations; Middle East; Soviet Union; United States; 1967-1973